การนำเสนอรูปแบบการพัฒนาคุณลักษณะภาวะผู้นำของผู้บริหารวิทยาลัยพยาบาล สังกัดกระทรวงสาธารณสุข - เบญจพร แก้วมีศรี (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
To propose a model on leadership traits development of nursing college administrators under the Ministry of Public Health. The research samples included 157 nursing college administrators, 32 directors and 125 vice-directors. The study consisted of 2 parts. Part one included study of roles, behaviors, and traits of nursing college administrators and part two was related to the development and verification of a model on leadership traits development of nursing college administrators under the Ministry of Public Health. The study of roles, behaviors, and traits of nursing college administrators revealed 40 leadership traits which were suitable for their roles. The model of leadership traits development consists of 7 stages. There were concept of leadership, leadership traits design, preparation of development, operation, post-development assessment, re-operation, and operational analysis. Each stage consisted of concept of development, content of development, objective, duration, trait development method, and result. The concept of leadership stage was to attain positive attitude and prepare leadership knowledge. The leadership traits design stage was to evaluate and assess leadership traits development. The preparation of development stage was to orient and prepare methods and situations for leadership traits development. The operation stage was to develop leadership knowledge, attitude, and skills in order to develop leadership traits need, which was composed of administrator image, knowledge related to management, management ability, and integration practice. The post-development assessment stage was to evaluate the suitability of developed leadership traits. The re-operation stage was to re-develop leadership knowledge, attitude, and skills that were inappropriately developed in the operation stage. Finally the operational analysis stage was to analyze the product of the operation in every stage, including the analysis of the whole process of the model.